TIBIAL PLATEAU FRACTURES–OUTCOME COMPARISON BETWEEN AUTOGRAFT AND TRICALCIUM PHOSPHATE - Dr.M. Ajithkumar, Dr Vijaykumar Angadi, Prof.(Dr.) M.Shantharam Shetty (Journal of Biomedical and Pharmaceutical Research, 2017)
Tibial plateau fractures are common injuries that result from indirect coronal and/or direct axial compressive forces The resulting fracture pattern is related to the age of the patient and their overall bone quality Guidelines in treating these fractures